PERAN PETANI KUNCI (COCOA DOCTOR) DALAM ADOPSI PAKET PENINGKATAN PRODUKSI PETANI KAKAO SERTIFIKASI - Sumiati, Sumiati; Arsyad, Muhammad; Diansari, Pipi (Jurnal Sosial Ekonomi Pertanian, 2018)
Abstract This study aims to determine: 1) the role of cocoa doctor in adoption production package; 2) cocoa farmer's response to the presence of cocoa doctor; 3) the level of adoption of production increasing package (called 3PP) of cocoa farmers. This research was conducted in Maliwowo Village, Eastern Luwu, South Sulawesi. Samples were 36 people, by simple random sampling method. The analysis employed scoring analysis. The results shows that: 1) the role of cocoa doctor in adoption 3PP in terms of information delivery, absorption ability of information, group planning, cooperation and group institutionalized is the middle category of 53.78%; 2) farmers have agreed response to the presence of cocoa doctor; and 3) farmers adoption levels to 3PP are in the medium category (75%). This implies that the role of cocoa doctor could be expected to improve adoption of 3PP. Keywords: cocoa doctor; cocoa farmers; adoption.